Remastering Sistem Operasi Android Untuk Peningkatan Performa Pada Lenovo A6000 Plus - Agus Irawan; Mey Risa; Tajuddin Noor (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2018)
Smartphone is a communication tool that is often used as a means of accessing information. Nowadays many Smartphones that can be used to record voice, take a picture and make a video with good quality. On a Smartphone, there are a wide variety of operating systems such as Symbian, Blackberry, Android, and iOS. Android is a Linux-based operating system for mobile devices that open source. Android also has many versions such as Gingerbread, ICS, Jelly Bean, KitKat, Lollipop, Marshmallow, Nougat and the latest Oreo. Not all samrtphone working optimally so harsher costum rom in order to maximize the ability of the smartphone. Remastering is a technique to change, add, delete application packages that are on an operating system. Remastering aims to make new android which has been optimized. The android operating system for multimedia can provide functionality to users especially in Lenovo A6000 PLUS in increasing ability